Membangun Ketahanan Sosial di Desa Serakapi: Sebuah Replikasi Model - Daud Bahransyaf; Ratih Probosiwi (Jurnal Penelitian Kesejahteraan Sosial, 2013)
As the expansion area, Serakapi Village needs to get facilities to support the development as its main area, Saneo Village. Strengthening human resources needed to run the village development programs by local social institutions in an attempt to embody social resilience. Through the Development of Village Social Resilience Model, that has been implemented by the Ministry of Social Affairs, social resilience in Serakapi Village was studied of its supporting and handicap factors. The results showed that the formed forum, namely Sabua Ade, had clear organized and planned in the division of social protection, community participation, social conflict prevention, and local wisdom development. This forum has been running well according to the plan despite one issue, funding problem. It’s recommended that community social resilience model should be aplicated in other regions by respecting the typology and character of the villages.